Attachment Anxiety as a Mediator Between Childhood Neglect and Intimate Partner Violence Victimization - Coder , Ana Amelia; Ngo, Trung-Hieu; Sutton, Joshua (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to examine whether attachment anxiety mediates the relationship between childhood neglect and intimate partner violence (IPV) victimization among adults in Canada.Methods and Materials: A descriptive correlational design was employed with a sample of 412 adults recruited from Canada, selected based on the Morgan and Krejcie sample size table. Standardized measures were used, including the Childhood Trauma Questionnaire–Short Form (CTQ-SF) for childhood neglect, the Experiences in Close Relationships–Revised (ECR-R) for attachment anxiety, and the Revised Conflict Tactics Scales (CTS2) for IPV victimization. Data were analyzed using SPSS version 27 and AMOS version 21. Pearson correlation analysis was performed to assess bivariate associations among variables, while Structural Equation Modeling (SEM) was used to test the hypothesized mediation model. Model fit was evaluated using χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices.Findings: Results revealed significant positive correlations between childhood neglect and attachment anxiety (r = .46, p < .001), childhood neglect and IPV victimization (r = .39, p < .001), and attachment anxiety and IPV victimization (r = .52, p < .001). The SEM analysis demonstrated good model fit (χ²/df = 2.01, GFI = .94, AGFI = .91, CFI = .96, TLI = .95, RMSEA = .049). Path analysis indicated that childhood neglect significantly predicted attachment anxiety (β = .46, p < .001), and attachment anxiety predicted IPV victimization (β = .41, p < .001). Childhood neglect also directly predicted IPV victimization (β = .22, p < .01). Mediation analysis confirmed that attachment anxiety partially mediated the relationship, with a significant indirect effect (β = .19, p < .001).Conclusion: These findings suggest that attachment anxiety is a key psychological mechanism linking childhood neglect to IPV victimization.